Development of binational radiation therapy quality indicator reports for prostate cancer treatment using registry data. Issue 8 (17th October 2022) - Chmiel, Edward; Pase, Marie; Evans, Melanie; Johnson, Maggie; Millar, Jeremy; Papa, Nathan
Abstract: Introduction: Quality indicators (QIs) are metrics which seek to allow comparison of clinicians' and institutes' practice to best evidence‐based practice. The Australia and New Zealand Prostate Cancer Outcomes Registry (PCOR–ANZ) is a bi‐national clinical quality registry with coverage estimated to be over 60% of the men newly diagnosed with prostate cancer. We outline the production and ambition of institute‐level QI reports to benchmark performance for radiation therapy in the treatment of prostate cancer. Methods: An expert clinician panel was assembled to create a list of candidate QIs based on a comprehensive literature review, and on modified Delphi‐method and expert‐consensus voting. A separate implementation group—including, clinicians, epidemiologists, data managers and data scientists—employed an evidence‐ and consensus‐ based approach to generate an effective QI report designed for automated production and regular distribution to participating institutes. Feedback from the recipient clinicians was sought to enable refinement of these reports. Results: Seven QIs, including three related to post‐treatment symptoms, were deemed feasible to analyse with the currently available data. Utilising an existing report template employed for benchmarking of surgical indicators, a novel radiation therapy report was generated using registry data in a secure analytical environment. The first, beta version of these reports have been produced and confidentially distributed. It is planned to automatically generate these reports biannually and iteratively refine them based on the clinician input. Conclusion: QI reports for the treatment of prostate cancer by radiation oncologists have been produced using data from Australia and New Zealand patients. These are being disseminated to institutes on a six‐monthly basis allowing comparisons to de‐identified peers. The reports aim to facilitate improving patient outcomes, deepen engagement with the radiation oncology community and increase the breadth of PCOR–ANZ coverage. Additional QIs will be included in future iterations of these reports as data matures.